INFLUENCE OF SILAGE ADDITIVES ON FERMENTATION OF HIGH MOISTURE CRIMPED CORN - Branislav Gálik; Daniel Bíro; Miroslav Juráček; Milan Šimko (Journal of Central European Agriculture, 2009)
The objective of this work was to find influence of different silage additives on silages fermentation and nutritional value made from high moisture crimped corn, which were conserved in semi experimental conditions. Three variants were examined, untreated control (C), and two experimental variants conserved by biological (variant A) and chemical (variant B) additives. The maize crimped corn was hermetically filled into plastic bins with the capacity 50 dm3. In silage conserved by additives was lower content of crude fibre (significantly in both experimental variants) and higher content of nitrogen free extract, starch and total sugars (significantly in variant A) established. In silages form both experimental variants we found significantly lower content of lactic acid. The highest concent we detected in silage conserved without additives. In silage conserved by biological inoculant we found lower content of acetic acid and higher content of butyric acid, but their content was generally very low. Additives used in the experiment decreased content of amonia (0.074 g.kg-1 in variant A and 0.095 g.kg-1 of dry matter in variant B) and alcohols too.